Free Radical Scavenging Activities of b-Sitosterol Extracted from Abies yuanbaoshanensis - He, Ruijie; Zou, Biqun; Fang, Hong; Zhang, Ye; Wu, Yingrui (Asian Journal of Chemistry, 2013)
From Abies yuanbaoshanensis, b-sitosterol was isolated and purified by column chromatography. The free radical scavenging activities of b-sitosterol were evaluated against DPPH, ABTS and hydroxyl radicals, respectively. The results showed that all IC50 of b-sitosterol were much lower than the standard value 10 mg/mL, demonstrating good radical scavenging activities of b-sitosterol.